Sodium-ion battery electrolyte, preparation method and application thereof
Patent Information
- Application Number
- CN202611085888.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]为解决常规钠离子电解液在60℃及以上高温环境下普遍存在溶剂易挥发、电极界面膜热脆开裂、副反应加剧、离子电导率骤降、热失控风险升高等问题,本发明提供了一种钠离子电池电解液及其制备方法和应用
本发明提供的钠离子电池电解液包括钠盐、非水有机溶剂、成膜添加剂以及除水除酸添加剂,其中,非水有机溶剂包括环酰胺类化合物、腈类化合物、砜类化合物,另外还含有限定含量的碳酸酯类辅助溶剂。在该电解液体系中,环酰胺化合物能够增强砜类化合物对钠盐的溶解性能,腈类化合物能弥补环酰胺类化合物耐高压氧化能力不足的问题,砜类化合物可抑制环酰胺类化合物与腈类化合物在高温条件下裂解降解;三者相互配合可产生单一溶剂不具备的协同增效效果。本发明提供的电解液兼顾离子传导与整体热稳定性能,有效延长电池循环寿命,显著优化了电池高温存储稳定性。性能测试结果显示,该钠离子电池电解液在高温储存6周后其色度涨幅远低于常规碳酸酯电解液;电解液初始电导率可达6.4~6.7 mS/cm,兼顾优异离子传导与合适粘度;在半电池测试中,搭载本发明提供的钠离子电池电解液的电池经300周充放电循环后容量保持率最高可达96%以上,相比常规碳酸电解液体系,循环容量衰减速率大幅降低。
Smart Images

Figure CN123018144A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary batteries, and specifically relates to a sodium-ion battery electrolyte, its preparation method, and its application. Background Technology
[0002] Sodium-ion batteries, with their abundant raw material reserves, low cost, and excellent safety, have become an ideal alternative power source for low-speed electric vehicles, energy storage power stations, and power batteries. Especially in high-temperature energy storage, outdoor operating conditions, and high-power discharge scenarios, stringent requirements are placed on the battery's high-temperature cycle stability and thermal safety. As the core component of sodium-ion batteries, the electrolyte not only directly affects the electrode interface state and ion transport rate but is also key to improving battery performance at high temperatures and solving high-temperature operation challenges. Currently, commercially available and research-under-development sodium-ion battery electrolytes primarily use carbonate-based solvent systems, supplemented by film-forming additives for interface regulation. Some high-temperature improvement schemes employ the addition of specific solvent components to enhance thermal stability or optimize at the additive level to improve interface performance. However, existing electrolyte systems are prone to the following problems at temperatures of 60°C and above: accelerated solvent evaporation and decomposition, easy rupture or failure of the electrode surface protective film at high temperatures, increased interfacial side reactions, significantly decreased ionic conductivity, and reduced battery thermal safety. These problems restrict the further development of sodium-ion batteries in high-temperature applications. Summary of the Invention
[0003] To address the common problems of conventional sodium-ion electrolytes at high temperatures of 60°C and above, such as easy solvent evaporation, thermal embrittlement and cracking of electrode interface films, aggravated side reactions, sharp drop in ionic conductivity, and increased risk of thermal runaway, this invention provides a sodium-ion battery electrolyte, its preparation method, and its application.
[0004] The technical solution provided by this invention is as follows: In a first aspect, the present invention provides a sodium-ion battery electrolyte, comprising: a sodium salt, a non-aqueous organic solvent, and additives, wherein the non-aqueous organic solvent comprises: cyclic amide compounds, nitrile compounds, and sulfone compounds, wherein: the volume percentage of the cyclic amide compounds in the non-aqueous organic solvent is 25% to 40%; and / or, the volume percentage of the nitrile compounds in the non-aqueous organic solvent is 30% to 45%; and / or, the volume percentage of the sulfone compounds in the non-aqueous organic solvent is 15% to 35%; and / or, the total volume percentage of the cyclic amide compounds, nitrile compounds, and sulfone compounds in the non-aqueous organic solvent is 80% to 90%.
[0005] In conjunction with the first aspect, in some embodiments, the cycloamide compounds include any one of 2-pyrrolidone and N-vinylpyrrolidone; the nitrile compounds include one or more of succinic anionibacterium, adiponitrile, glutaronitrile, and 2-methylglutaronitrile; and the sulfone compounds include one or more of sulfolane, dimethyl sulfone, and diethyl sulfone.
[0006] In conjunction with the first aspect, in some embodiments, the non-aqueous organic solvent further includes a carbonate auxiliary solvent, wherein the volume percentage of the carbonate auxiliary solvent in the non-aqueous organic solvent is 10% to 20%, and the carbonate auxiliary solvent includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0007] In conjunction with the first aspect, in some embodiments, the additives include film-forming additives and dehydrating and deacidifying additives. The film-forming additives include two or more of fluoroethylene carbonate, vinylene carbonate, and 1,3-propanesulfonic acid lactone, and the dehydrating and deacidifying additives include one or more of hexamethyldisilazane and vinylene carbonate trimer.
[0008] In conjunction with the first aspect, in some embodiments, the film-forming additive has a mass percentage content of 0.8% to 2.5% in the sodium-ion battery electrolyte; and / or, the water-removing and acid-removing additive has a mass percentage content of 0.2% to 0.5% in the sodium-ion battery electrolyte.
[0009] In conjunction with the first aspect, in some embodiments, the sodium salt includes one or more of sodium hexafluorophosphate and sodium difluorosulfonamide, wherein the molar concentration of the sodium salt in the sodium-ion battery electrolyte is 1.0 mol / L to 1.5 mol / L.
[0010] Secondly, the present invention provides a method for preparing a sodium-ion battery electrolyte, comprising the following steps: Cycloamide compounds, nitrile compounds, sulfone compounds, and carbonate auxiliary solvents are stirred and mixed for a short time to obtain a mixed base solvent; Sodium salt was added to the above mixed base solvent in portions, and the mixture was stirred continuously for a second time until it was completely dissolved, thus obtaining a salt-containing base electrolyte. Add film-forming additives and dehydration and deacidification additives to the above-mentioned salt-containing basic electrolyte, stir and mix for a third time to obtain a mixed solution; The above-mentioned mixed solution was filtered and allowed to stand to obtain a sodium-ion battery electrolyte.
[0011] In conjunction with the second aspect, in some embodiments, the above preparation steps are all carried out in an inert gas protected environment, and the water content in the environment is less than 0.1 ppm.
[0012] In conjunction with the second aspect, in some implementations, the first time is 20 to 40 minutes; and / or, the second time is 50 to 70 minutes; and / or, the third time is 30 to 50 minutes.
[0013] Thirdly, the present invention provides a sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and the aforementioned sodium-ion battery electrolyte.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects: The sodium-ion battery electrolyte provided by this invention comprises sodium salt, non-aqueous organic solvent, film-forming additive, and dehydration and deacidification additive. The non-aqueous organic solvent includes cyclic amide compounds, nitrile compounds, and sulfone compounds, and also contains a limited amount of carbonate auxiliary solvent. In this electrolyte system, cyclic amide compounds enhance the solubility of sulfone compounds in sodium salt, nitrile compounds compensate for the insufficient high-voltage oxidation resistance of cyclic amide compounds, and sulfone compounds inhibit the degradation of cyclic amide and nitrile compounds under high-temperature conditions. The synergistic effect of these three compounds is not achieved by a single solvent. The electrolyte provided by this invention balances ion conduction and overall thermal stability, effectively extending battery cycle life and significantly optimizing battery high-temperature storage stability. Performance test results show that the sodium-ion battery electrolyte exhibits a much lower color increase than conventional carbonate electrolytes after 6 weeks of high-temperature storage; the initial conductivity of the electrolyte reaches 6.4~6.7 mS / cm, balancing excellent ion conduction with suitable viscosity; in half-cell tests, batteries equipped with the sodium-ion battery electrolyte provided by this invention retain up to 96% of their capacity after 300 charge-discharge cycles, significantly reducing the cycle capacity decay rate compared to conventional carbonate electrolyte systems. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 Comparison chart of capacity retention after 300 cycles at 60°C, using electrolytes from Examples 1, 2, 3, and 4 of this invention and Comparative Examples 1, 2, and 3 assembled into NFPP batteries. Figure 2 The figure shows the AC impedance spectroscopy results of the electrolytes of Examples 1, 4, Comparative Example 1 and Comparative Example 2 of the present invention after being assembled into NFPP batteries and cycled at 60°C for 100 cycles. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0018] In a first aspect, the present invention provides a sodium-ion battery electrolyte, comprising: a sodium salt, a non-aqueous organic solvent, and additives, wherein the non-aqueous organic solvent comprises: cyclic amide compounds, nitrile compounds, and sulfone compounds, wherein: the volume percentage of the cyclic amide compounds in the non-aqueous organic solvent is 25% to 40%; and / or, the volume percentage of the nitrile compounds in the non-aqueous organic solvent is 30% to 45%; and / or, the volume percentage of the sulfone compounds in the non-aqueous organic solvent is 15% to 35%; and / or, the total volume percentage of the cyclic amide compounds, nitrile compounds, and sulfone compounds in the non-aqueous organic solvent is 80% to 90%. Preferably, the volume percentage of the cyclic amide compounds in the non-aqueous organic solvent is 32%, the volume percentage of the nitrile compounds in the non-aqueous organic solvent is 33%, and the volume percentage of the sulfone compounds in the non-aqueous organic solvent is 20%.
[0019] The cyclic amides, nitriles, and sulfones in this electrolyte system exhibit synergistic effects. Cycloamides enhance the solubility of sulfones in sodium salts, nitriles compensate for the insufficient high-pressure oxidation resistance of cyclic amides, and sulfones inhibit the degradation of cyclic amides and nitriles under high-temperature conditions. Each component can compensate for the defects in interface, ion dissociation, and thermal stability that exist when used alone, producing a synergistic effect not found in single solvents.
[0020] In some embodiments, the cycloamide compounds include any one of 2-pyrrolidone and N-vinylpyrrolidone; the nitrile compounds include one or more of succinic anionibacterium, adiponitrile, glutaronitrile, and 2-methylglutaronitrile; and the sulfone compounds include one or more of sulfolane, dimethyl sulfone, and diethyl sulfone.
[0021] Preferably, the nitrile compound is succinic anionibacterium, the cyclic amide compound is 2-pyrrolidone, and the sulfone compound is sulfolane. Compared to other nitrile compounds, succinic anionibacterium has superior ionic conductivity, film-forming ability, and lower cost; compared to N-vinylpyrrolidone, 2-pyrrolidone has high stability, high polarity, and good solubility; compared to other sulfone compounds, sulfolane has good solubility, antioxidant properties, and thermal stability, and can actively participate in and optimize the interfacial chemistry of the battery.
[0022] In some embodiments, the non-aqueous organic solvent further includes a carbonate auxiliary solvent, wherein the volume percentage of the carbonate auxiliary solvent in the non-aqueous organic solvent is 10% to 20%, and the carbonate auxiliary solvent includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0023] In the sodium-ion battery electrolyte system provided by this invention, the overall viscosity of the compound solvents consisting of cycloamides, nitriles, and sulfones is relatively high. Adding 10%–20% low-content carbonate effectively reduces the viscosity of the sodium-ion battery electrolyte system, improving sodium salt dissociation efficiency and low-temperature ionic conductivity. Compared to traditional electrolytes dominated by carbonates, the electrolyte system provided by this invention contains only 10%–20% carbonate. Simultaneously, the high thermal stability of sulfone compounds, the positive electrode passivation effect of nitriles, and the negative electrode film-forming ability of cycloamide compounds form a triple protective barrier, encapsulating the carbonate component and significantly suppressing high-temperature decomposition and interfacial side reactions of carbonates, overcoming the inherent defects of traditional carbonate electrolytes.
[0024] In some embodiments, the additives include film-forming additives and dehydrating and deacidifying additives. The film-forming additives include two or more of fluoroethylene carbonate, vinylene carbonate, and 1,3-propanesulfonic acid lactone. The dehydrating and deacidifying additives include any one of hexamethyldisilazane and vinylene carbonate trimer.
[0025] Preferably, the film-forming additives are fluoroethylene carbonate and 1,3-propanesulfonic acid lactone, and the dehydration and deacidification additive is hexamethyldisilazane. The three components work synergistically to simultaneously construct an organic-inorganic hybrid bilayer interfacial film on the positive and negative electrode surfaces. A flexible SEI film is formed on the negative electrode, and a dense CEI film is formed on the positive electrode, overcoming the limitation of a single additive providing only unilateral protection and effectively adapting to the interfacial environment of the positive and negative electrodes in a ternary solvent system. This hybrid film has a dense structure, effectively blocking the co-intercalation of highly polar cyclic amides, nitriles, and sulfone solvents, avoiding the continuous decomposition and electrolyte loss at high temperatures caused by uneven film formation with a single additive. Simultaneously, the hybrid film possesses excellent high-temperature resistance and resistance to volume expansion, and is not prone to brittle fracture and detachment during long cycling. Combined with a ternary high-thermal-stability solvent, it can significantly delay capacity decay. Furthermore, the multi-component additives can synergistically capture trace amounts of moisture and hydrogen fluoride impurities, blocking chain side reactions and inhibiting high-temperature discoloration of the electrolyte.
[0026] In some embodiments, the film-forming additive has a mass percentage content of 0.8% to 2.5% in the sodium-ion battery electrolyte; and / or, the dehydration and deacidification additive has a mass percentage content of 0.2% to 0.5% in the sodium-ion battery electrolyte. Preferably, the film-forming additive has a mass percentage content of 2% in the sodium-ion battery electrolyte, and the dehydration and deacidification additive has a mass percentage content of 0.3% in the sodium-ion battery electrolyte.
[0027] The film-forming additives undergo reduction and decomposition on the negative electrode surface, constructing a dense, flexible, and highly conductive SEI passivation film. This prevents continuous reduction side reactions between the negative electrode active material and the electrolyte. Simultaneously, it synergistically optimizes the positive electrode interface with nitrile components, aiding in the formation of a stable CEI film, inhibiting high-pressure solvent oxidation and transition metal dissolution, reducing interfacial impedance, and improving the battery's initial cycle efficiency and long-term cycle stability. The dehydration and deacidification additives remove trace amounts of water from the electrolyte system, blocking the chain reaction of sodium salt hydrolysis to hydrofluoric acid. They also complex with acidic impurities such as hydrofluoric acid generated in the system, preventing acid corrosion of electrode materials and aluminum current collectors, and avoiding damage to the SEI / CEI interface film. This reduces cell gas expansion and continuously increasing internal resistance, leading to failure issues. These two types of additives work synergistically, simultaneously achieving electrode interface protection and system impurity purification in the sodium-ion battery electrolyte provided by this invention, improving the electrolyte's thermal stability, high-pressure oxidation resistance, and battery cycle life.
[0028] In some embodiments, the sodium salt includes one or more of sodium hexafluorophosphate and sodium difluorosulfonyl imide, and the molar concentration of the sodium salt in the sodium-ion battery electrolyte is 1.0 mol / L to 1.5 mol / L. Preferably, the sodium salt is sodium difluorosulfonyl imide, and its molar concentration in the sodium-ion battery electrolyte is 1.2 mol / L. Compared to sodium hexafluorophosphate, which decomposes above 60°C, sodium difluorosulfonyl imide exhibits superior high-temperature stability.
[0029] This invention also provides a method for preparing a sodium-ion battery electrolyte, comprising the following steps: Cycloamide compounds, nitrile compounds, sulfone compounds, and carbonate auxiliary solvents are stirred and mixed for a short time to obtain a mixed base solvent; Sodium salt was added to the above mixed base solvent in portions, and the mixture was stirred continuously for a second time until it was completely dissolved, thus obtaining a salt-containing base electrolyte. Add film-forming additives and dehydration and deacidification additives to the above-mentioned salt-containing basic electrolyte, stir and mix for a third time to obtain a mixed solution; The above-mentioned mixed solution was filtered and allowed to stand to obtain a sodium-ion battery electrolyte.
[0030] In some embodiments, the preparation steps are all carried out in an inert gas protected environment, and the water content in the environment is less than 0.1 ppm. Since the electrolyte system provided in this invention is a sodium ion electrolyte, and both water and oxygen can trigger a series of irreversible side reactions such as sodium salt hydrolysis, solvent decomposition, electrode corrosion, and interface degradation; the inert gas can isolate oxygen and control the ambient water content to below 0.1 ppm, thereby suppressing the above-mentioned side reactions.
[0031] In some embodiments, the first time is 20-40 min; and / or, the second time is 50-70 min; and / or, the third time is 30-50 min. Preferably, the first time is 30 min, the second time is 60 min, and the third time is 40 min.
[0032] The present invention also provides a sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and the sodium-ion battery electrolyte described above.
[0033] Example 1 In an argon-protected glove box with water and oxygen content both less than 0.1 ppm, 1.6 mL of 2-pyrrolidone, 1.65 mL of succinate, and 1.0 mL of sulfolane were taken in the following volume ratios: 0.5 mL of ethyl methyl carbonate and 0.25 mL of dimethyl carbonate. All solvent components were transferred to a reaction vessel and stirred at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0034] 1.122 g of sodium bis(fluorosulfonyl)imide (NaFSI) was added to the base solvent obtained above. The system was kept at a constant temperature of 25°C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was observed. Three additives were then added sequentially to the electrolyte system after the sodium salt was dissolved: first, 0.0772 g of film-forming compound additives fluoroethylene carbonate (FEC) and 0.0514 g of 1,3-propanesulfonyl lactone (PS) were added; then, 0.0193 g of dehydrating and deacidifying additive hexamethyldisilazane (HMDS) was added. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture. The mixture was filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0035] Example 2 In an argon-protected glove box with water and oxygen content both less than 0.1 ppm, 1.25 mL of 2-pyrrolidone, 1.5 mL of succinate, and 1.25 mL of sulfolane were taken in the following volume ratios: 0.6 mL of ethyl methyl carbonate and 0.4 mL of dimethyl carbonate. All solvent components were transferred to a reaction vessel and stirred at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0036] 1.122 g of NaFSI was added to the base solvent obtained above, and the system was kept at a constant temperature of 25°C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was observed. Three additives were then added sequentially to the electrolyte system after dissolving the sodium salt: first, 0.0777 g of film-forming compound additives FEC and 0.0518 g of PS were added, followed by 0.0194 g of dehydration and deacidification additive HMDS. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture. The mixture was then filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0037] Example 3 In an argon-protected glove box with water and oxygen contents both less than 0.1 ppm, 1.75 mL of 2-pyrrolidone, 2 mL of succinate, and 0.75 mL of sulfolane were weighed in sequence according to the volume ratio. Then, 0.3 mL of ethyl methyl carbonate and 0.2 mL of dimethyl carbonate, two carbonate auxiliary solvents, were weighed in separately. All solvent components were transferred to a reaction vessel and stirred and mixed at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0038] 1.122 g of NaFSI was added to the base solvent obtained above, and the system was kept at a constant temperature of 25°C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was observed. Three additives were then added sequentially to the electrolyte system after the sodium salt was dissolved: first, 0.0764 g of film-forming compound additives FEC and 0.0510 g of PS were added, followed by 0.0191 g of dehydration and deacidification additive HMDS. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture. The mixture was then filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0039] Example 4 In an argon-protected glove box with water and oxygen content both less than 0.1 ppm, 1.6 mL of N-vinylpyrrolidone, 1.65 mL of adiponitrile, and 1 mL of molten dimethyl sulfone were weighed in sequence according to the volume ratio. Then, 0.5 mL of ethyl methyl carbonate and 0.25 mL of dimethyl carbonate, two carbonate auxiliary solvents, were weighed separately. All solvent components were transferred to a reaction vessel and stirred and mixed at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0040] 1.122 g of NaFSI was added to the base solvent obtained above, and the system was kept at a constant temperature of 25 °C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was formed. Three additives were then added sequentially to the electrolyte system after the sodium salt was dissolved: first, 0.0768 g of film-forming compound additives FEC and 0.0512 g of PS were added, followed by 0.0192 g of dehydration and deacidification additive HMDS. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture. The mixture was then filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0041] Comparative Example 1 In an argon-protected glove box with water and oxygen contents both less than 0.1 ppm, 1.5 mL of ethylene carbonate, 1.5 mL of methyl ethyl carbonate, and 2 mL of dimethyl carbonate were weighed in sequence according to the volume ratio. All solvent components were transferred into the reaction vessel and stirred at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0042] Add 0.836 g of sodium hexafluorophosphate (NaPF6) to the obtained base solvent, maintain a constant temperature of 25°C, and stir continuously for 60 min until the NaPF6 is completely dissolved and no solid precipitate forms. Add two additives sequentially to the electrolyte system after dissolving the sodium salt: first add 0.0646 g of film-forming compound additive FEC and 0.0323 g of vinylene carbonate (VC). After addition, stir continuously for 40 min to ensure all additives are fully dispersed in the electrolyte, resulting in a homogeneous mixture. Filter the mixture using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, allow it to stand and stabilize, finally obtaining a conventional carbonate-based sodium-ion battery electrolyte.
[0043] Comparative Example 2 In an argon-protected glove box with water and oxygen contents both less than 0.1 ppm, 1.75 mL of 2-pyrrolidone and 2 mL of succinic anhydride, a binary main solvent, were weighed in sequence according to the volume ratio. Then, 0.75 mL of ethyl methyl carbonate and 0.5 mL of dimethyl carbonate, two carbonate auxiliary solvents, were weighed in separately. All solvent components were transferred to a reaction vessel and stirred and mixed at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0044] 1.122 g of NaFSI was added to the base solvent obtained above, and the system was kept at a constant temperature of 25°C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was observed. Three additives were then added sequentially to the electrolyte system after the sodium salt was dissolved: first, 0.0742 g of film-forming compound additives FEC and 0.0495 g of PS were added, followed by 0.0186 g of dehydration and deacidification additive HMDS. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture. The mixture was then filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0045] Comparative Example 3 In an argon-protected glove box with water and oxygen content both less than 0.1 ppm, 1.6 mL of 2-pyrrolidone, 1.65 mL of succinic anhydride, and 1.0 mL of sulfolane were weighed in sequence according to the volume ratio. Then, 0.5 mL of ethyl methyl carbonate and 0.25 mL of dimethyl carbonate, two carbonate auxiliary solvents, were weighed in separately. All solvent components were transferred to a reaction vessel and stirred and mixed at room temperature for 30 min to prepare a basic mixed solvent with uniform components.
[0046] 1.122 g of NaFSI was added to the base solvent obtained above, and the system was kept at a constant temperature of 25°C and stirred continuously for 60 min until the NaFSI was completely dissolved and no solid precipitate was observed. 0.129 g of film-forming additive FEC was added to the electrolyte system after the sodium salt was dissolved. After the addition was complete, the mixture was stirred continuously for 40 min to ensure that all additives were fully dispersed in the electrolyte, resulting in a homogeneous mixture of all components. The mixture was filtered using a 0.01 μm precision filter membrane to remove trace amounts of insoluble impurities. After filtration, the mixture was allowed to stand and stabilize, finally yielding the sodium-ion battery electrolyte.
[0047] Performance testing: To evaluate the high-temperature stability of the sodium-ion battery electrolyte provided by this invention, the electrolytes in the comparative examples and embodiments described above were prepared and transferred to sealed glass bottles. These bottles were then placed in a high-purity inert gas environment with a water content of less than 0.1 ppm and an oxygen content of less than 0.1 ppm for 6 weeks of high-temperature storage before sampling and testing. The colorimetric (unit: Hazen) test was conducted using the platinum-cobalt colorimetric method. Initially, the colorimetric values of all electrolyte samples were below 10 Hazen, and they appeared transparent to the naked eye with no significant differences. However, after 6 weeks of high-temperature long-term storage, the colorimetric values of Examples 1-4 ranged from 28.9 to 36.2 Hazen, showing only a small change. In contrast, the colorimetric values of Comparative Examples 1-3 increased significantly, with Comparative Example 1 showing a sharp increase to 94.1 Hazen. These results indicate that the sodium-ion electrolyte provided by this invention can effectively inhibit decomposition and deterioration under high-temperature conditions, exhibiting excellent high-temperature stability.
[0048] Furthermore, the conductivity (unit: mS / cm) of the sodium-ion battery electrolyte in the above embodiments was tested, and the test results are shown in Table 1.
[0049] Table 1. High-temperature storage stability and room-temperature conductivity data of electrolyte Regimen Color (Hazen) / after formulation Color (Hazen) / after 6 weeks storage Conductivity (mS / cm) / after formulation Example 1 4.7 28.9 6.7 Example 2 5.6 36.2 6.4 Example 3 5.5 33.5 6.5 Example 4 4.8 31.7 6.6 Comparative Example 1 3.5 94.1 7.1 Comparative Example 2 4.2 62.5 7.0 Comparative Example 3 4.9 57.3 6.3 As shown in Table 1, the high-temperature thermal stability of all examples is superior to that of the comparative examples, achieving a balance between conductivity and thermal stability. After 6 weeks of high-temperature storage, the chromaticity of comparative examples 1, 2, and 3 increased from 3.5, 4.2, and 4.9 Hazen to 94.1, 62.5, and 57.3 Hazen, respectively, with a maximum chromaticity change rate of 2588.57%. In contrast, the chromaticity change rate of the electrolytes corresponding to examples 1-4 was controlled within 600%. Regarding room-temperature conductivity, comparative examples 1 and 2, due to their lower system viscosity, exhibited higher initial conductivity of 7.1 mS / cm and 7.0 mS / cm, respectively, but their high-temperature stability was poor. The room-temperature conductivity of examples 1-4 remained stable at 6.4-6.7 mS / cm, with example 1 showing the highest conductivity at 6.7 mS / cm and ranking second in thermal stability, demonstrating outstanding overall performance.
[0050] To verify the actual high-temperature compatibility of the electrolyte provided by this invention in sodium-ion batteries, coin cells were assembled using Na4Fe3(PO4)2P2O7 (NFPP) as the positive electrode and metallic sodium as the negative electrode. The CR2032 coin cell assembly was completed in an argon glove box (H2O less than 0.1 ppm, O2 less than 0.1 ppm). After the batteries were allowed to stand for 4 hours, they were subjected to high-temperature charge-discharge cycle tests at 60°C. The test results are shown in Table 2.
[0051] Table 2. High-temperature cycling and room-temperature 3C discharge performance of CR2032 coin cell. Regimen Ambient 3C discharge capacity retention (%) High temperature 300 cycle capacity retention (%) Example 1 88.8 96.24 Example 2 86.5 93.11 Example 3 84.2 94.63 Example 4 85.1 93.87 Comparative Example 1 91.3 58.70 Comparative Example 2 88.1 79.25 Comparative Example 3 89.2 83.62 As shown in Table 2, all embodiments of the present invention have achieved significant improvements in high-temperature cycling stability while maintaining excellent room-temperature rate discharge performance, and their overall electrochemical performance is superior to that of the comparative examples.
[0052] Regarding rate performance at room temperature, the electrolyte provided by this invention did not show significant degradation. Comparative Example 1 exhibited the highest capacity retention rate at 3C at room temperature, at 91.3%; Comparative Examples 3 and 2 were 89.2% and 88.1%, respectively. Example 1 showed a capacity retention rate of 88.8% at room temperature, slightly lower than Comparative Example 1, but the remaining examples all remained stable above 84%, indicating that the electrolyte provided by this invention demonstrates good stability in maintaining high rate performance.
[0053] Regarding high-temperature cycling stability, such as Figure 1 As shown, after 300 cycles of high temperature cycling, the capacity retention of all embodiments remained stable at over 93%. Specifically, Embodiment 1 achieved a capacity retention of 96.24%; Embodiments 2, 3, and 4 achieved 93.11%, 94.63%, and 93.87%, respectively. In contrast, the highest capacity retention among all comparative examples was only 83.62%, with Comparative Example 1 at only 58.70%. Embodiment 1 demonstrated a 37.54% higher capacity retention rate during high temperature cycling compared to Comparative Example 1.
[0054] In summary, the electrolyte formulation provided by this invention effectively solves the industry pain point that traditional electrolytes struggle to balance room temperature rate performance and high temperature cycling stability.
[0055] To further verify the interfacial stability of the ternary system at high temperatures, AC impedance spectroscopy was performed on CR2032 coin cells cycled at 60℃. The test results are as follows: Figure 2 As shown, the semicircular diameters at mid-to-high frequencies are in the order of Comparative Example 1 > Comparative Example 2 > Example 4 > Example 1. This indicates that Example 1 has the lowest charge transfer resistance and the best interfacial electrochemical reaction kinetics, followed by Example 4, while Comparative Examples 1 and 2 have greater charge transfer resistance. In the low-frequency Warburg diffusion section, the curves of Examples 1 and 4 have steeper slopes, and their ion diffusion rates are significantly better than those of the comparative examples. These results indicate that Examples 1 and 4 can simultaneously reduce charge transfer resistance and accelerate ion diffusion, and their electrochemical performance is far superior to that of Comparative Examples 1 and 2, with Example 1 exhibiting the best overall performance.
[0056] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.
[0057] It should be noted that in this invention, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.
[0058] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features of the invention herein.
Claims
1. A sodium-ion battery electrolyte, comprising: Sodium salts, non-aqueous organic solvents, and additives, characterized in that the non-aqueous organic solvents comprise: cyclic amide compounds, nitrile compounds, and sulfone compounds, wherein: The cyclic amide compound has a volume percentage of 25% to 40% in the non-aqueous organic solvent; and / or, The nitrile compound has a volume percentage of 30% to 45% in the non-aqueous organic solvent; and / or, The sulfone compound has a volume percentage content of 15% to 35% in the non-aqueous organic solvent; and / or, The total volume percentage of the cycloamide compound, the nitrile compound, and the sulfone compound in the non-aqueous organic solvent is 80% to 90%.
2. The sodium-ion battery electrolyte according to claim 1, characterized in that, The cycloamide compounds include any one of 2-pyrrolidone and N-vinylpyrrolidone; the nitrile compounds include one or more of succinic anionyl, adiponitrile, glutaronitrile, and 2-methylglutaronitrile; and the sulfone compounds include one or more of sulfolane, dimethyl sulfone, and diethyl sulfone.
3. The sodium-ion battery electrolyte according to claim 1, characterized in that, The non-aqueous organic solvent also includes carbonate auxiliary solvents, wherein the volume percentage of the carbonate auxiliary solvent in the non-aqueous organic solvent is 10% to 20%, and the carbonate auxiliary solvent includes one or more of dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.
4. The sodium-ion battery electrolyte according to claim 1, characterized in that, The additives include film-forming additives and dehydrating and deacidifying additives. The film-forming additives include two or more of fluoroethylene carbonate, vinylene carbonate, and 1,3-propanesulfonic acid lactone. The dehydrating and deacidifying additives include one or more of hexamethyldisilazane and vinylene carbonate trimer.
5. The sodium-ion battery electrolyte according to claim 4, characterized in that, The film-forming additive has a mass percentage content of 0.8% to 2.5% in the sodium-ion battery electrolyte; and / or, the water-removing and acid-removing additive has a mass percentage content of 0.2% to 0.5% in the sodium-ion battery electrolyte.
6. The sodium-ion battery electrolyte according to claim 1, characterized in that, The sodium salt includes one or more of sodium hexafluorophosphate and sodium difluorosulfonamide, and the molar concentration of the sodium salt in the sodium-ion battery electrolyte is 1.0 mol / L to 1.5 mol / L.
7. A method for preparing a sodium-ion battery electrolyte, characterized in that, Includes the following steps: Cycloamide compounds, nitrile compounds, sulfone compounds, and carbonate auxiliary solvents are stirred and mixed for a short time to obtain a mixed base solvent; Sodium salt was added to the mixed base solvent in portions, and the mixture was stirred continuously for a second time until it was completely dissolved, to obtain a salt-containing base electrolyte. Add film-forming additives and dehydration and deacidification additives to the salt-containing basic electrolyte, stir and mix for a third time to obtain a mixed solution; The mixed solution was filtered and allowed to stand to obtain the sodium-ion battery electrolyte.
8. The preparation method according to claim 7, characterized in that, All preparation steps were carried out in an inert gas protected environment, and the water content in the environment was less than 0.1 ppm.
9. The preparation method according to claim 7, characterized in that, The first time is 20-40 min; and / or, the second time is 50-70 min; and / or, the third time is 30-50 min.
10. A sodium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and the sodium-ion battery electrolyte according to any one of claims 1 to 6.
